(k, m)-type slant helices for partially null and pseudo null curves in Minkowski space E14 - Bektas, Mehmet; Yilmaz, Munevver Yildirim (Walter de Gruyter Gmbh, 2020)
In this study we define the notion of (k, m)-type slant helices in Minkowski 4-space and express some characterizations for partially and pseudo null curves in E-1(4).
Keywords: Difference equations; rational difference equations